تقسسيما الشاطبي للمقاصد الشرعية وتصنيفه الأحكام الفقهية والخلقية تحتها : دراسة تحليلية نقدية - Abduul-Mawla Mohamad M.A Kheblil (Universiti Sains Islam Malaysia, 2024)
The study seeks to consolidate the link between the shariah objectives (maqasid), including the three levels of (necessities, needs and luxuries), and juristic rulls and ethical rulls of the shariah. The study aims to analyze at Shatibi’s classification of maqasid, especially his classification of jurisprudential and ethic Islamic rulings as luxuries while they can be upgraded to the necessity level. The study highlights his criteria to distinguish the three level and their relations, and clarifies the confusion in arranging the rulings in the three levels.The study executes the inductive approach by examining al- Shatibi’s views’ in his book (al-Mwafaqaat) to conclude his criteria to classify the maqasid and then to apply these criteria. The analytical qualitative method is implemented as well to analyze and extrapolate al-Shatibi’s views about the classification. Furthermore, the critical method is also implemented by a comprehensive examination of the topic of the study. The findings reveal that al-Shatibi classified the maqasid based on many aspects, mainly the combination of the duty bearer (mukallaf) and his intention which relates to the shariah’s purpose. The findings also reveal that some of al- Shatibi’s classifications of the jurisprudential rulings, classified by al- Shatibi’s as luxuries, are more appropriate to be upgraded to the level of necessity or at least to the level of needs. Examining the ethic rulings is another significant finding. The study finds that the behavioral rulings vary as some rulings are reflected on the key morals which the shariah objectives classify as necessity level while behavioral rulings which based on noble moral traits can be classified as luxuries.